Pengaruh Change Management Factors terhadap Organizational Innovation Di mediasi oleh Sustainable Competitive Advantages - Karina Ganadi; Netania Emilisa (Universitas Batanghari, 2022)
This study aims to analyze the effect of Change Management Factors on Sustainable Competitive Advantages mediated by Organizational Innovation on students in West Jakarta. The data collected were 267 students from private universities in West Jakarta. This study uses four dimensions on the variables of Change Management Factors namely, Organizational Goal, Transformational Leadership, Participation and Communication, and Education and Training. The data collection technique used in this research is non-probability sampling with purposive sampling method. The measurement tool in this study is an interval scale with a Likert scale technique (from a scale of 1 to 5). Instrumental tests were carried out in the form of validity, reliability, and conformity tests using SPSS version 22. The research method used was Structural Equation Model with AMOS, the results of this study stated that: 1). Organizational Goal has a positive influence on Organizational Innovation. 2). Transformational Leadership has no positive influence on Organizational Innovation. 3). Participation and Communication has a positive influence on Organizational Innovation. 4). Education and Training has a positive influence on Organizational Innovation. 5). Organizational Innovation has a positive influence on Sustainable Competitive Advantages. 6). Organizational Goal has a positive influence on Sustainable Competitive Advantages mediated by Organizational Innovation. 7). Transformational Leadership has no positive influence on Sustainable Competitive Advantages mediated by Organizational Innovation. 8). Participation and Communication has a positive influence on Sustainable Competitive Advantages mediated by Organizational Innovation. 9). Education and Training has a positive influence on Sustainable Competitive Advantages mediated by Organizational Innovation.